ETIOLOGY AND PATHOGENESIS OF ANKYLOSING SPONDYLITIS IN KAZAKHSTAN - Shafiee, Darya (Nazarbayev University School of Medicine, 2025)
Spondyloarthropathies (SpA) is a group of rheumatic inflammatory autoimmune diseases. The most frequent and the most disabling SpA is ankylosing spondylitis (AS). AS causes fusion of the axial skeleton, constant pain, and peripheral manifestations. AS is considered a multifactorial disease; to date, no clear diagnostic marker has been linked to its pathogenesis. The HLA-B*27 gene is one of the well-known predisposing factors for the development of AS. By using HLA-B*27 alleles' genotyping, this work aimed to contribute to a more comprehensive understanding of the genetic factors influencing the development and progression of AS in Kazakhstani AS patients. Another trigger for the disease is the altered microbiome composition and its impact on the gut and systemic immune response. Therefore, the second aim of this work was to evaluate the composition of the microbiome of AS individuals compared to healthy participants. Overall, this study established the significant role of the HLA-B*27 alleles in the susceptibility to AS in the Kazakhstani population and conducted an in-depth exploratory taxonomic and functional analysis of gut microbiome composition as another potential trigger for the disease within this population.
Keywords: type of access: embargo; spondyloarthritis; SpA; ankylosing spondylitis; AS; HLA-B27; genotyping; microbiome; metagenomics; shotgun sequencing